1991
DOI: 10.1128/jcm.29.10.2357-2359.1991
|View full text |Cite
|
Sign up to set email alerts
|

Detection of salmonellae by using Rambach agar and by a C8 esterase spot test

Abstract: In food microbiology, Rambach agar facilitates the differentiation of non-typhi Salmonella through a specific red pigmentation of the colonies. The usefulness of Rambach agar was examined relative to its usefulness to the field of clinical microbiology. Of 170 non-typhi SalmoneUa strains, 92 and 97% gave bright red colonies after 24 and 48 h of incubation, respectively, while 100% of 112 other members of the family Enterobacteriaceae were of a different color (blue, green, beige, or colorless). Red colonies we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

1993
1993
1999
1999

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 2 publications
0
11
0
Order By: Relevance
“…T h e sensitivities of the MUCAP, SM-ID, Rambach and Hektoen agar tests were 100, 93, 88 and 99%, respectively, and their specificities were 74, 97, 76 and 59%, respectively. Other authors have reported similarly high rates of sensitivity and specificity of these chromogenic media using pure Salmonella strains (Freydiere and Gille 1991 ;Grunewald et al 1991).…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…T h e sensitivities of the MUCAP, SM-ID, Rambach and Hektoen agar tests were 100, 93, 88 and 99%, respectively, and their specificities were 74, 97, 76 and 59%, respectively. Other authors have reported similarly high rates of sensitivity and specificity of these chromogenic media using pure Salmonella strains (Freydiere and Gille 1991 ;Grunewald et al 1991).…”
Section: Resultsmentioning
confidence: 65%
“…(1991) and Davies and Wray (1994). Comparative studies using these media were carried out by Freydiere and Gille (1991), Manafi and Sommer (1992), and Dusch and Altwegg (1993).…”
Section: Introductionmentioning
confidence: 99%
“…One method for identifying Salmonella spp. in the clinical laboratory involves the use of methylumbelliferyl caprylate (MUCAP), a substrate that fluoresces upon hydrolysis of the ester bond (1,8,11,22). This substrate can be used to distinguish salmonellae from other bacteria, including Escherichia, Enterobacter, Yersinia, and Shigella spp.…”
Section: Resultsmentioning
confidence: 99%
“…The appearance of blue fluorescence under UV light within 1 min of application was observed for all Salmonella test strains; however, colonies of some Pseudomonas and Acinetobacter spp. also fluoresced (6). Thus, although the sensitivity of the MUCAP test was high (100%), the specificity was low (80%), especially compared to that of a latex slide agglutination test (96%) (9).…”
mentioning
confidence: 94%